Enhancing project-based learning in engineering education: a hybrid DT-CDIO-RA framework for sustainable product design - P. Hariharasakthisudhan; K. Logesh; K. Sathickbasha; Sathish Kannan (Discover Education)
Abstract This study presents a structured hybrid framework integrating Design Thinking (DT), the Conceive-Design-Implement-Operate (CDIO) methodology, and Root Assessment (RA) to enhance project-based learning (PBL) in engineering education. The framework addresses limitations in conventional PBL by embedding iterative ideation, structured engineering processes, and systematic decision-making. Applied to the development of a Seed Injecting Machine, the framework enabled students to engage in user-centric design, sustainability-driven decision-making, and iterative prototyping. The DT phase guided empathy-driven ideation, while CDIO structured concept realization through detailed design, fabrication, and testing. RA facilitated a multi-criteria evaluation process, prioritizing technical feasibility, sustainability, and user adoption metrics. This methodology provided a robust PBL model, aligning experiential learning with real-world constraints. Students gained hands-on expertise in interdisciplinary problem-solving, stakeholder-driven design, and sustainability assessment. The proposed DT-CDIO-RA framework enhances engineering education by bridging theoretical learning with applied innovation, equipping learners with competencies critical for sustainable product development.